Preparation method of microcrystalline silicon layer, HJT solar cell and manufacturing method of HJT solar cell
By using N2O as an oxygen source for oxygen doping during the manufacturing process of the microcrystalline silicon layer, the poor crystallinity and cell attenuation problems caused by CO2 are solved, and higher crystallinity, conductivity and coating speed are achieved, improving the performance and production efficiency of solar cells.
Patent Information
- Application Number
- CN202311363950.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
When CO2 is used as an oxygen source in the prior art, the crystallinity of the microcrystalline silicon layer is poor, the crystallization rate is reduced, the gas utilization rate is low, the coating speed is slow, and the C content in the film layer is increased after dissociation, resulting in a higher battery attenuation.
N2O is used as an oxygen source for oxygen doping, instead of CO2 in the prior art, oxygen doping is performed in situ during the manufacturing process of the microcrystalline silicon layer to realize the production of an oxygen-doped P-type or N-type microcrystalline silicon layer.
By using N2O to improve the crystallinity and conductivity of the microcrystalline silicon layer, the reduction of film layer quality and battery attenuation caused by CO2 dissociation is avoided, and the coating speed is improved, production capacity is improved and costs are reduced.
Smart Images

Figure CN119866087A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cell manufacturing, and relates to a method for preparing a microcrystalline silicon layer, a HJT solar cell and a manufacturing method thereof. Background Art
[0002] The P region of a traditional HJT solar cell is a region where an intrinsic i layer and a boron-doped amorphous P layer are grown on the back of a silicon substrate. An inversion layer is formed on an N-type silicon substrate through the P layer to construct a PN junction at the NP interface, thereby obtaining the ability to separate electrons and holes and realizing the conversion of light energy into electrical energy.
[0003] However, the traditional amorphous P layer is an amorphous layer, the boron effective doping efficiency is low, the field passivation ability is weak, and the amorphous conductivity is poor, which is basically in an insulating state. Therefore, the holes in the amorphous P layer are basically in a longitudinal tunneling transmission perpendicular to the film layer. Therefore, with the development of technology, microcrystalline P layer is often used to replace amorphous P layer, so that the boron effective doping ability can be significantly improved, the field passivation ability and conductivity can be enhanced, and the battery performance can be improved in terms of Uoc, FF and Rs.
[0004] Furthermore, moderately doping the microcrystalline P layer with oxygen can allow the doped oxygen to increase the narrowed bandgap width of the microcrystalline P layer, thereby optimizing the energy level relationship with the adjacent layer structure and further improving Uoc and Rs.
[0005] At present, the new oxygen-doped microcrystalline P layer is made of CO 2 As an oxygen source. However, using CO 2 When used as an oxygen source, there are the following problems: first, it will lead to poor crystallinity of the microcrystalline layer and reduced crystallization rate; second, CO 2 Dissociation is more difficult, gas utilization is low, and the coating speed is relatively slow; thirdly, after dissociation, it is easy to increase the C content in the film layer, resulting in higher battery attenuation.
[0006] Therefore, it is necessary to develop a new technical solution for preparing oxygen-doped microcrystalline silicon layers in order to support and improve the performance of HJT solar cells. Summary of the invention
[0007] In view of the problems existing in the prior art, the object of the present invention is to provide a method for preparing a microcrystalline silicon layer, a HJT solar cell and a manufacturing method thereof. The method for preparing a microcrystalline silicon layer comprises: in the process of preparing the microcrystalline silicon layer, using N 2 O is used as an oxygen source for oxygen doping. The present invention uses laughing gas to replace the CO 2 , in situ oxygen doping of the microcrystalline silicon layer during its manufacturing process can realize the manufacture of an oxygen-doped P-type microcrystalline silicon layer or an N-type microcrystalline silicon layer; by using N 2O effectively improves the crystallinity and conductivity of the microcrystalline silicon layer, avoiding the 2 Dissociation causes the C content in the film to increase, resulting in poor film quality and high battery attenuation. 2 O is easier to dissociate, which can effectively increase the coating speed, which is beneficial to increasing production capacity and reducing costs.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a microcrystalline silicon layer, the preparation method comprising:
[0010] In the process of preparing the microcrystalline silicon layer, N 2 O is used as an oxygen source for oxygen doping.
[0011] The present invention uses laughing gas N 2 O replaces CO in existing technology 2 As an oxygen source, oxygen doping is performed on the microcrystalline silicon layer in situ during the manufacturing process of the microcrystalline silicon layer, so that the manufacture of oxygen-doped P-type microcrystalline silicon layer or N-type microcrystalline silicon layer can be realized; 2 Compared with the existing technology as an oxygen source, the present invention can effectively improve the 2 The problem of poor film crystallinity caused by CO 2 The dissociation causes the C content in the film layer to increase, thereby preventing the battery attenuation caused by the deterioration of the film quality; using N 2 O also has the advantage of being more easily dissociated, so it is more efficient than using CO 2 , the coating rate is improved, and N can be effectively reduced 2 O usage, which is beneficial to increase production capacity and reduce costs.
[0012] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] As a preferred technical solution of the present invention, the microcrystalline silicon layer is prepared using silane and hydrogen as raw materials.
[0014] Preferably, the flow ratio of the silane to the hydrogen (hydrogen dilution ratio) is 1:(30-500), for example 1:30, 1:50, 1:80, 1:100, 1:130, 1:150, 1:180, 1:200, 1:230, 1:250, 1:280, 1:300, 1:330, 1:350, 1:380, 1:400, 1:430, 1:450, 1:480 or 1:500, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0015] Preferably, the silane and the N 2 The flow ratio of O is 100:(1-100), for example, 100:1, 100:3, 100:5, 100:8, 100:10, 100:13, 100:15, 100:18, 100:20, 100:23, 100:25, 100:28, 100:30, 100:35, 100:38, 100:40, 100:45, 100:48, 100:51 , 100:55, 100:58, 100:62, 100:66, 100:69, 100:72, 100:75, 100:78, 100:81, 100:84, 100:87, 100:90, 100:93, 100:95, 100:98 or 100:100, but are not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0016] Preferably, the flow rate of silane is 10 to 1000 sccm, for example, 10 sccm, 50 sccm, 80 sccm, 100 sccm, 200 sccm, 300 sccm, 400 sccm, 500 sccm, 600 sccm, 700 sccm, 800 sccm, 900 sccm or 1000 sccm, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0017] As a preferred technical solution of the present invention, at the same time as the oxygen doping, a P-type doping source or an N-type doping source is used to perform P-type doping or N-type doping.
[0018] Preferably, the P-type doping source includes a boron source.
[0019] Preferably, the boron source comprises borane.
[0020] Preferably, the N-type doping source includes a phosphorus source.
[0021] Preferably, the phosphorus source comprises phosphine.
[0022] Preferably, the flow ratio of the P-type doping source to the silane is (1-80):100, for example, 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, 50:100, 55:100, 60:100, 65:100, 70:100, 75:100 or 80:100, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0023] Preferably, the flow ratio of the N-type doping source to the silane is (50-900):100, for example, 50:100, 80:100, 100:100, 150:100, 200:100, 250:100, 300:100, 350:100, 400:100, 450:100, 500:100, 550:100, 600:100, 650:100, 700:100, 750:100, 800:100, 850:100 or 900:100, etc., but is not limited to the listed values, and other values not listed within the above numerical range are equally applicable.
[0024] It should be noted that the present invention uses silane, borane or phosphine, which can be passed into the reaction system in the form of pure gas or can be passed into the reaction system after forming a mixed gas with hydrogen, but the total flow rate or total volume of each raw material should meet the preferred flow ratio or volume ratio range. Exemplarily, when using phosphine, a phosphine / hydrogen mixed gas with a volume ratio of 1%, 2% or 6% of phosphine can be used, and when the phosphine / hydrogen mixed gas is passed into the reaction system, the ratio of the flow rate (volume) of phosphine to the total flow rate (volume) of hydrogen in the system should meet (50-900):100.
[0025] It should be noted that whether using laughing gas or CO in the prior art 2 As oxygen sources, both have optimal usage and doping amounts. Excessive usage will lead to excessive conversion of the film into SiO x The conductivity is very poor. Considering that the N layer (N-type microcrystalline silicon layer) on the front is the front light-transmitting layer, the oxygen source doping amount needs to be higher, while the P layer (P-type microcrystalline silicon layer) as the back film layer does not need to consider light transmittance, and only needs to ensure band matching, so the doping amount is relatively small. Therefore, when using N 2 When preparing N-type microcrystalline silicon layer, silane and N 2 The flow ratio of O is preferably 100:(10-100). 2 When preparing P-type microcrystalline silicon layer, silane and N 2 The flow ratio of O is preferably 100:(5 to 50).
[0026] In a second aspect, the present invention provides a method for manufacturing a HJT solar cell, wherein the manufacturing method uses the preparation method described in the first aspect.
[0027] As a preferred technical solution of the present invention, the manufacturing method comprises:
[0028] Silicon wafers are textured, intrinsic i layers are prepared on both sides, N-type layers are prepared on the front side, P-type layers are prepared on the back side, TCO layers are prepared on both sides, and electrodes are prepared on both sides to obtain HJT solar cells;
[0029] The N-type layer and / or the P-type layer is an N-type microcrystalline silicon layer or a P-type microcrystalline silicon layer obtained by the preparation method described in the first aspect.
[0030] The present invention uses N 2 The oxygen-doped P-type microcrystalline silicon layer obtained by using N O is mainly used to increase the band gap width, so that it can match the potential barrier formed between the intrinsic i layers after it increases to a certain extent, thereby improving the transmission obstruction caused by the potential barrier, thereby achieving the purpose of reducing Rs. At the same time, the present invention also found that the use of N 2 Oxygen doping of the P-type microcrystalline silicon layer and the N-type microcrystalline silicon layer is beneficial to the improvement of the crystallization rate and conductivity, and can improve the attenuation of battery performance to a certain extent, which is beneficial to improving the overall output power and conversion efficiency of the component.
[0031] Therefore, in the present invention, it is preferred that the P-type layer in the HJT battery is made of N 2 O prepared by oxygen-doping P-type microcrystalline silicon layer, on this basis, the N-type layer can also be made of N 2 O prepared by oxygen-doped N-type microcrystalline silicon layer, the battery can achieve the best optimization and improvement effect.
[0032] In addition, since the N-type microcrystalline silicon is located on the front side of the battery, oxygen doping can improve the light transmittance of the microcrystalline silicon, while a small amount of oxygen doping on the back side is mainly to adjust the electrical gain brought by the band gap. Therefore, preferably, the oxygen doping amount of the N-type microcrystalline silicon layer is greater than the oxygen doping amount of the P-type microcrystalline silicon layer.
[0033] As a preferred technical solution of the present invention, the preparation method divides the microcrystalline silicon layer into at least two superimposed sub-layers and prepares them sequentially.
[0034] Preferably, the first sublayer prepared is not doped with oxygen, and the remaining sublayers are doped with N 2 O is used as an oxygen source for oxygen doping.
[0035] Preferably, the thickness of the first sub-layer prepared initially accounts for 15% to 25% of the total thickness of the microcrystalline silicon layer, for example 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0036] Preferably, the first and last sublayers are not doped with oxygen, and the remaining sublayers are doped with N 2 O is used as an oxygen source for oxygen doping.
[0037] As a preferred technical solution of the present invention, when the N-type layer is the N-type microcrystalline silicon layer, the thickness is 5 to 40 nm, for example, 5 nm, 8 nm, 12 nm, 15 nm, 18 nm, 22 nm, 25 nm, 27 nm, 30 nm, 33 nm, 36 nm, 38 nm or 40 nm, and the refractive index is 2.3 to 3.5, for example, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4 or 3.5, but is not limited to the listed values, and other values not listed within the above numerical range are equally applicable.
[0038] Preferably, when the N-type layer is not the N-type microcrystalline silicon layer, the N-type layer includes an N-type amorphous silicon layer and / or a phosphorus-doped microcrystalline SiO x layer.
[0039] Preferably, the refractive index of the N-type amorphous silicon layer is 3.5-4.2, for example, 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.1 or 4.2, but is not limited to the listed values, and other values not listed in the above range are also applicable.
[0040] Preferably, the phosphorus-doped microcrystalline SiO x The refractive index of the layer is 2.3 to 3.5, for example 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4 or 3.5, but is not limited to the listed values, and other values not listed within the above range are also applicable.
[0041] As a preferred technical solution of the present invention, when the P-type layer is the P-type microcrystalline silicon layer, the thickness is 10 to 100 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or 100 nm, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are equally applicable.
[0042] As a preferred technical solution of the present invention, the N-type microcrystalline silicon layer and / or the P-type microcrystalline silicon layer are divided into three sublayers stacked in sequence, the first sublayer prepared is not doped with oxygen, and the remaining sublayers are all doped with N 2 O is used as an oxygen source for oxygen doping.
[0043] Preferably, the first and last sublayers are not doped with oxygen, and the middle sublayers are doped with N 2 O is used as an oxygen source for oxygen doping.
[0044] Preferably, the thickness of the first sublayer prepared is 2 to 20 nm, for example 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm, the thickness of the middle sublayer is 2 to 45 nm, for example 2 nm, 5 nm, 8 nm, 11 nm, 18 nm, 21 nm, 24 nm, 27 nm, 30 nm, 33 nm, 36 nm, 39 nm, 42 nm or 45 nm, and the thickness of the last sublayer prepared is 3 to 35 nm, for example 3 nm, 6 nm, 9 nm, 12 nm, 15 nm, 18 nm, 21 nm, 24 nm, 27 nm, 30 nm, 33 nm or 35 nm, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0045] Exemplarily, the P-type microcrystalline silicon layer is divided into a P1 layer, a P2 layer and a P3 layer stacked in sequence, the P1 layer is not doped with oxygen, and the P2 layer and the P3 layer are both doped with N 2 O is used as an oxygen source for oxygen doping. Further, the P1 layer and the P3 layer are not oxygen doped, and the P2 layer uses N 2 Similarly, when the N-type layer is an N-type microcrystalline silicon layer, the N-type microcrystalline silicon layer may also be configured as a plurality of superimposed sublayers as required, for example, it may be divided into an N1 layer, an N2 layer and an N3 layer, wherein the N1 layer and the N3 layer may not be oxygen doped, and the N2 layer may be oxygen doped using laughing gas.
[0046] It should be noted that the present invention is preferably divided into two sub-layers. This solution is superior to the structure with only one layer: the single-layer microcrystalline p film layer cannot take into account the contact between the i / p layer and the p / TCO layer while having low resistance, while the double-layer structure can appropriately take into account and adjust. The ideal structure is that the P1 layer is not oxygen-doped, so that P1 can form a better contact with the i layer and obtain a lower contact resistance.
[0047] In addition, the contact resistance between p / TCO cannot reach the best effect due to the oxygen doping of the second layer in the double-layer structure. Therefore, preferably, the three-layer structure is more ideal, which can take into account both the lower contact resistance between i / p and the contact resistance between p / TCO. Therefore, the ideal structure is that the P1 layer is not doped with oxygen, so that the band gaps of the i layer and the p layer are similar before they form a good crystallization, and then the transition from P1 to the P2 with better crystallinity requires oxygen doping to compensate for the band gap mismatch caused by good crystallinity. Finally, the P3 layer is not doped with oxygen and heavily doped, so that a good contact is formed between p / TCO.
[0048] In addition, the N-layer microcrystalline silicon layer has the same technical effect and will not be further described here.
[0049] Preferably, the growth rate of the N-type microcrystalline silicon layer and the P-type microcrystalline silicon layer is 0.05-0.5nm / s, for example, 0.05nm / s, 0.08nm / s, 0.1nm / s, 0.13nm / s, 0.16nm / s, 0.18nm / s, 0.20nm / s, 0.24nm / s, 0.28nm / s, 0.33nm / s, 0.35nm / s, 0.38nm / s, 0.40nm / s, 0.43nm / s, 0.46nm / s, 0.48nm / s or 0.5nm / s, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0050] As a preferred technical solution of the present invention, the silicon wafer comprises an N-type silicon wafer.
[0051] Preferably, the method for preparing the intrinsic i-layer comprises a CVD method.
[0052] Preferably, the thickness of the intrinsic i layer is 5 to 20 nm, for example 5 nm, 8 nm, 11 nm, 13 nm, 15 nm, 17 nm, 19 nm or 20 nm, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0053] Preferably, the refractive index of the intrinsic i-layer is 3.4-4.0, for example, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9 or 4.0, but is not limited to the listed values, and other values not listed in the above range are also applicable.
[0054] Preferably, the method of preparing the TCO layer comprises PVD and / or RPD.
[0055] Preferably, the TCO layer includes any one of indium tin oxide, cerium-doped indium oxide or aluminum-doped zinc oxide, or a composite layer formed by superposition of at least two of them, for example, it can be a composite layer of indium tin oxide and cerium-doped indium oxide, a composite layer of aluminum-doped zinc oxide and indium tin oxide, or a composite layer of cerium-doped indium oxide and aluminum-doped zinc oxide.
[0056] Preferably, the thickness of the TCO layer is 70 to 100 nm, for example, 70 nm, 73 nm, 76 nm, 79 nm, 82 nm, 85 nm, 88 nm, 91 nm, 94 nm, 97 nm or 100 nm, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0057] Preferably, the refractive index of the TCO layer is 1.7 to 2.2, such as 1.7, 1.8, 1.9, 2, 2.1 or 2.2, but is not limited to the listed values, and other values not listed within the above range are also applicable.
[0058] Preferably, the electrode comprises a silver grid line with a grid line width of 5 to 3000 μm, for example, 5 μm, 10 μm, 30 μm, 50 μm, 80 μm, 120 μm, 180 μm, 260 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, 1200 μm, 1400 μm, 1600 μm, 180 0μm, 2000μm, 2200μm, 2400μm, 2600μm, 2800μm or 3000μm, etc., height 10-100μm, for example 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or 100μm, etc., but are not limited to the listed values, other unlisted values within the above numerical range are also applicable.
[0059] Preferably, the manufacturing method further comprises injecting LED light into the obtained HJT solar cell to repair damage to the film layer.
[0060] In a third aspect, the present invention provides a HJT solar cell obtained using the manufacturing method described in the second aspect.
[0061] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0062] With the use of CO 2 Compared with the existing technology as an oxygen source, the present invention can effectively improve the 2 The problem of poor film crystallinity caused by CO 2Dissociation causes the C content in the film layer to increase, thereby preventing the battery attenuation caused by the deterioration of the film quality; using N 2 O can also increase the coating rate and effectively reduce N 2 O usage, which is beneficial to increase production capacity and reduce costs.
[0063] The present invention uses N 2 O manufacturing oxygen-doped P-type microcrystalline silicon layer in HJT cells can effectively increase its band gap width, improve the transmission obstruction caused by barrier obstacles, and reduce Rs. 2 O The simultaneous manufacture of N-type microcrystalline silicon layer and P-type microcrystalline silicon layer is beneficial to the improvement of crystallization rate and conductivity, and can improve the attenuation of battery performance to a certain extent, thereby improving the overall output power and conversion efficiency of the component. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 is a schematic diagram of a HJT battery structure according to an embodiment;
[0065] Figure 2 is a schematic diagram of a HJT battery structure according to another embodiment;
[0066] Figure 3 is a graph showing the relationship between the storage time and efficiency of the batteries obtained in Example 2 and Comparative Example 3;
[0067] Figure 4 is a graph showing the relationship between the storage time and efficiency of the batteries obtained in Example 9 and Comparative Example 6;
[0068] Figure 5 1 is a graph showing the relationship between the storage time and efficiency of the batteries obtained in Example 10 and Comparative Example 7.
[0069] 1. Silicon substrate; 2. First intrinsic i-layer; 3. Second intrinsic i-layer; 4. N-type layer; 5. P-type layer; 6. First TCO layer; 7. Second TCO layer; 8. First electrode; 9. Second electrode; 51. First sub-P-type layer; 52. Second sub-P-type layer; 53. Third sub-P-type layer; DETAILED DESCRIPTION
[0070] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0071] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0072] It should be understood that, in the description of the present invention, the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.
[0073] In some specific embodiments, the present invention provides a method for preparing a microcrystalline silicon layer, the preparation method comprising:
[0074] In the process of preparing the microcrystalline silicon layer, N 2 O is used as an oxygen source for oxygen doping.
[0075] In one embodiment, the microcrystalline silicon layer is prepared using silane and hydrogen as raw materials.
[0076] In one embodiment, the flow ratio of the silane to the hydrogen (hydrogen dilution ratio) is 1:(30-500).
[0077] In one embodiment, the silane and the N 2 The flow ratio of O is 100:(1~100).
[0078] In one embodiment, the flow rate of the silane is 10-1000 sccm.
[0079] In one embodiment, P-type doping or N-type doping is performed using a P-type doping source or an N-type doping source simultaneously with the oxygen doping.
[0080] In one embodiment, the P-type doping source includes a boron source, and the boron source includes borane.
[0081] In one embodiment, the N-type doping source includes a phosphorus source, and the phosphorus source includes phosphine.
[0082] In one embodiment, the flow ratio of the P-type doping source to the silane is (1-80): 100. In one embodiment, the flow ratio of the N-type doping source to the silane is (50-900):100.
[0083] In addition, for HJT solar cell structures, as shown in the attached Figure 1 The HJT solar cell includes a silicon substrate 1, and a first intrinsic i layer 2, an N-type layer 4, a first TCO layer 6, and a first electrode 8 located on one side of the silicon substrate 1, and a second intrinsic i layer 3, a P-type layer 5, a second TCO layer 7, and a second electrode 9 located on the other side of the silicon substrate 1.
[0084] In some specific embodiments, the present invention provides a method for manufacturing a HJT solar cell, wherein the manufacturing method uses the method for preparing a microcrystalline silicon layer provided in the above embodiment.
[0085] In one embodiment, the manufacturing method comprises:
[0086] Silicon wafers are textured, intrinsic i layers are prepared on both sides, N-type layers are prepared on the front side, P-type layers are prepared on the back side, TCO layers are prepared on both sides, and electrodes are prepared on both sides to obtain HJT solar cells;
[0087] The N-type layer and / or the P-type layer is an N-type microcrystalline silicon layer or a P-type microcrystalline silicon layer obtained by using the method for preparing a microcrystalline silicon layer provided in the above embodiment.
[0088] In one embodiment, when the N-type layer is the N-type microcrystalline silicon layer, the thickness is 5 to 40 nm.
[0089] In one embodiment, when the N-type layer is not the N-type microcrystalline silicon layer, the N-type layer includes an N-type amorphous silicon layer and / or a phosphorus-doped microcrystalline SiO x layer.
[0090] In one embodiment, the refractive index of the N-type amorphous silicon layer is 3.5 to 4.2; the phosphorus-doped microcrystalline SiO x The refractive index of the layer is 2.3 to 3.5.
[0091] In one embodiment, when the P-type layer is the P-type microcrystalline silicon layer, the thickness is 10 to 100 nm.
[0092] In one embodiment, the preparation method divides the microcrystalline silicon layer into at least two superimposed sub-layers and prepares them sequentially, wherein the first sub-layer prepared first is not doped with oxygen, and the remaining sub-layers are all doped with N 2 O is used as an oxygen source for oxygen doping; further, the first and last sublayers prepared are not oxygen doped, and the remaining sublayers are all doped with N 2 O is used as an oxygen source for oxygen doping.
[0093] In one embodiment, when the preparation method forms a multi-layer structure of the microcrystalline silicon layer, if the thickness of the first sublayer is too thin, it will affect the contact resistance, and if the thickness of the first sublayer is too thick, the wide band gap field passivation of the oxygen-doped layer in the transmission energy band will be weakened, which is not conducive to the gain of the oxygen-doped layer on the switching voltage. Therefore, preferably, the thickness of the first sublayer prepared first accounts for 15% to 25% of the total thickness of the microcrystalline silicon layer.
[0094] In one embodiment, if Figure 2 As shown, the N-type microcrystalline silicon layer and / or the P-type microcrystalline silicon layer are divided into three sub-layers stacked in sequence, namely, a first sub-P-type layer 51, a second sub-P-type layer 52, and a third sub-P-type layer 53. The first sub-layer prepared is not doped with oxygen, and the remaining sub-layers are all doped with N 2 O is used as an oxygen source for oxygen doping; further, the first and last sublayers prepared are not oxygen doped, and the middle sublayer uses N 2 O is used as an oxygen source for oxygen doping.
[0095] In one embodiment, the thickness of the first sub-layer prepared is 2-20 nm, and the thickness of the last sub-layer prepared is 3-35 nm.
[0096] In one embodiment, the growth rate of the N-type microcrystalline silicon layer and the P-type microcrystalline silicon layer is 0.05-0.5 nm / s.
[0097] In one embodiment, the silicon wafer comprises an N-type silicon wafer.
[0098] In one embodiment, the method of preparing the intrinsic i-layer comprises a CVD method.
[0099] In one embodiment, the thickness of the intrinsic i-layer is 5-20 nm.
[0100] In one embodiment, the refractive index of the intrinsic i-layer is 3.4-4.0.
[0101] In one embodiment, the method of preparing the TCO layer includes PVD and / or RPD.
[0102] In one embodiment, the TCO layer includes any one of indium tin oxide, cerium-doped indium oxide, or aluminum-doped zinc oxide, or a composite layer formed by stacking at least two of them.
[0103] In one embodiment, the thickness of the TCO layer is 70-100 nm.
[0104] In one embodiment, the refractive index of the TCO layer is 1.7 to 2.2.
[0105] In one embodiment, the electrode comprises silver grid lines, and the grid line width is 5 to 3000 μm.
[0106] In one embodiment, the manufacturing method further comprises injecting LED light into the obtained HJT solar cell to repair film damage.
[0107] In one embodiment, the method for manufacturing the HJT solar cell includes:
[0108] (1) Select a textured N-type silicon wafer and coat the intrinsic i layer on both sides by CVD method, the thickness of the intrinsic i layer on one side is 5 to 20 nm, and the refractive index is controlled to be 3.4 to 4.0;
[0109] (2) Use SiH 4 , H 2 , PH 3 and N 2 O, controlled SiH 4 The flow rate is 10~1000sccm, controlling SiH 4 With H 2 The flow ratio is 1:(30~500), controlling SiH 4 With N 2 O flow ratio is 100:(1~100), controlling pH 3 With SiH 4 The flow ratio is (50-900):100; an N-type microcrystalline silicon layer is prepared on the front intrinsic i layer, with a thickness of 5-40 nm and a refractive index of 2.0-3.5;
[0110] (3) Re-use of SiH 4 , H 2 , B 2 H 6 and N 2 O, controlled SiH 4 The flow rate is 10~1000sccm, controlling SiH 4 With H 2 The flow ratio is 1:(30~500), controlling SiH 4 With N 2 The flow ratio of O is 100:(1~100), controlling B 2 H 6 With SiH 4 The flow ratio is (1-80):100, and the preparation time is controlled to be 50-500s, and a P-type microcrystalline silicon layer is formed on the intrinsic i layer on the back side;
[0111] (4) using the PVD method, a layer of indium tin oxide TCO is plated on both sides, with a thickness of 70 to 100 nm and a refractive index of 1.7 to 2.2;
[0112] (5) Printing silver grid lines on both sides, controlling the grid line width to be 5 to 3000 μm and the height to be 10 to 100 μm, forming positive and negative electrodes, and then injecting LED light to repair the film damage caused during the preparation process, completing the preparation of the battery, and obtaining a HJT solar cell.
[0113] Furthermore, in one embodiment, step (3) of the method for manufacturing the HJT solar cell comprises:
[0114] (3-1) Use of SiH 4 , H 2 and B 2 H 6 (i.e. control of SiH 4 With N 2 O flow ratio is 100:0), controlling SiH 4 The flow rate is 10~1000sccm, controlling SiH 4 With H 2 The flow ratio is 1:(30~500), control B 2 H 6 With SiH 4 The flow ratio is (1-80):100, and the preparation time is controlled to be 50-500s, and the P1 layer is prepared on the intrinsic i layer on the back side;
[0115] (3-2) Re-use of SiH 4 , H 2 , B 2 H 6 and N 2 O, controlled SiH 4 The flow rate is 10~1000sccm, controlling SiH 4 With H 2 The flow ratio is 1:(30~500), control B 2 H 6 With SiH 4 The flow ratio is (1~80):100, controlling SiH 4 With N 2 The flow ratio of O is 100:(1-100), and the P2 layer is prepared on the P1 layer;
[0116] The obtained P1 and P2 form a P-type microcrystalline silicon layer.
[0117] Furthermore, in one embodiment, the method for manufacturing the HJT solar cell further comprises, in step (3):
[0118] (3-3) Use of SiH 4 , H 2 and B 2 H 6 (i.e. control of SiH4 With N 2 O flow ratio is 100:0), controlling SiH 4 The flow rate is 10~1000sccm, controlling SiH 4 With H 2 The flow ratio is 1:(30~500), control B 2 H 6 With SiH 4 The flow ratio is (1-80):100, the preparation time is controlled to be 50-500s, and the P3 layer is prepared on the P2 layer;
[0119] The obtained P1, P2 and P3 form a P-type microcrystalline silicon layer.
[0120] In another specific embodiment, the present invention provides a HJT solar cell, and the HJT solar cell is obtained using the manufacturing method of the HJT solar cell provided in the above-mentioned specific embodiment.
[0121] Examples 1-4
[0122] Embodiments 1-4 all provide a HJT solar cell, wherein the HJT solar cell is obtained based on a method for preparing a microcrystalline silicon layer and a method for manufacturing a HJT solar cell using the same provided in a specific embodiment; in the method for manufacturing the HJT solar cell, when forming a P-type microcrystalline silicon layer, SiH 4 With N 2 The flow ratios of O were 100:10, 100:5, 100:15 and 100:20 respectively, and other conditions were kept unchanged to obtain Examples 1-4.
[0123] Comparative Example 1
[0124] This comparative example provides a HJT solar cell, wherein the manufacturing method of the HJT solar cell does not use N 2 Except for O, other conditions are exactly the same as those in Example 1.
[0125] Comparative Examples 2-5
[0126] Comparative Examples 2-5 all provide a HJT solar cell, wherein the manufacturing method of the HJT solar cell is different from that of Examples 1-4 in that 2 O replaced by CO 2 Except for this, other conditions remain the same as those in the corresponding embodiment.
[0127] Table 1 records the preparation parameters and film properties of the P-type microcrystalline silicon layer obtained in step (3) of Examples 1-4 and Comparative Examples 1-5. The total thickness Tks (nm) and the refractive index n are measured by using a full-spectrum ellipsometer, and the coating rate (nm / s) = total thickness Tks (nm) / total coating time t (s); the crystallization rate F is measured by coating on high-temperature resistant organic glass and then using a Raman tester with a wavelength of 532nm to test the crystallization curve, at 480cm -1 , 510nm -1 and 520nm -1 The Gaussian curve is fitted at the position, and then the integral area of the three Gaussian curves is used to calculate: crystallization rate F = (area (510nm -1 )+Area(520nm -1 )) / Sanfeng(480cm -1 , 510nm -1 and 520nm -1 ) area; the resistance is tested by using a high resistance tester to directly test the film resistance, with a positive and negative electrode distance of 1cm on the film surface and a voltage of 225V.
[0128] Table 1
[0129]
[0130] Note: "×" in Table 1 means the resistance is too large, usually in the GΩ level, and it is considered non-conductive.
[0131] It can be seen from Table 1 that:
[0132] The coating speed (coating rate) of doped nitrous oxide will be accelerated by about 8.84% (based on the CO 2 The average plating rate of the four groups and the N-doped 2 O), the faster plating rate also means an 8.84% increase in production efficiency; and under the same refractive index or similar refractive index conditions, such as around 3.55 / 3.45 / 3.30, the corresponding CO 2 / N 2 The flow ratio values of O are 20 / 10, 30 / 20, and 40 / 30, that is, N 2 The amount of O is significantly reduced, and N doping 2 The single film resistance of O is relatively low, and both its crystallinity and conductivity are advantageous.
[0133] Table 2 records the performance data of HJT solar energy obtained in Examples 1 and 2 and Comparative Examples 2 and 3. The data are the test results of the Weixin IV tester. The cells were made of M6-sized silicon wafers and calibrated with standard wafers before testing. The conversion efficiency Eta, open-circuit voltage Uoc, fill factor FF, short-circuit current Isc and DC resistance Rs are all medians after multiple tests.
[0134] Table 2
[0135]
[0136] From the comparison of electrical properties in Table 2, it can be seen that N-doped 2 O and CO doping 2 When the refractive index is equal or close, use N 2 The electrical performance of the battery obtained by O treatment is improved, mainly manifested in the reduction of Rs due to the conductivity advantage, thereby effectively gaining FF. The results in Table 2 are consistent with those in Table 1.
[0137] Figure 3 The relationship between the storage time and efficiency of the batteries obtained in Example 2 and Comparative Example 3 is shown in the figure. The horizontal axis is the number of days of storage, the bar is the efficiency value, and the broken line is the attenuation value. It can be seen from the figure that compared with the use of CO 2 , using nitrous oxide for oxygen doping to obtain a P-type microcrystalline silicon layer, the battery performance decays more slowly and has better stability.
[0138] Embodiment 5-8
[0139] Embodiments 5-8 all provide a HJT solar cell, and the HJT solar cell is obtained based on a method for preparing a microcrystalline silicon layer and a method for manufacturing an HJT solar cell using the same provided in a specific embodiment; in the method for manufacturing the HJT solar cell, when forming a P-type microcrystalline silicon layer, a P1 layer and a P2 layer stacked on the P1 layer are sequentially manufactured in two steps, and the P1 layer and the P2 layer form a P-type microcrystalline silicon layer; when manufacturing the P1 layer, SiH 4 With N 2 The flow ratio of O is 100:0 (i.e., no N 2 O, without oxygen doping), 100:7.14, 100:14.29 and 100:21.43, keeping other conditions unchanged, to obtain Examples 5-8.
[0140] Table 3
[0141]
[0142] It can be seen from Table 3 that when the P-type microcrystalline silicon layer is divided into multiple sub-layers and the P1 layer is not oxygen-doped, its contact resistance has an obvious advantage.
[0143] Examples 9-10
[0144] Examples 9-10 all provide a HJT solar cell, which is obtained based on a method for preparing a microcrystalline silicon layer and a method for manufacturing a HJT solar cell using the same provided in a specific embodiment; in the method for manufacturing the HJT solar cell, when forming an N-type microcrystalline silicon layer, a VHF (very high frequency) power supply and an RF (high frequency) power supply are used respectively, and other conditions are kept unchanged, thereby obtaining Examples 9-10.
[0145] Comparative Examples 6-7
[0146] Comparative Examples 6-7 all provide a HJT solar cell. The HJT solar cell manufacturing method uses CO 2 Alternative N 2 O and SiH 4 With CO 2 The flow ratio is set to 100:(10 to 200) CO 2 Except for the optimum value of oxygen doping, other conditions are exactly the same as those of Example 9 and Example 10.
[0147] Figure 4 and Figure 5 The figures are the relationship between the storage time and efficiency of the batteries obtained in Example 9 and Comparative Example 6 and Example 10 and Comparative Example 7, respectively. The horizontal axis is the number of days of storage, the bar is the efficiency value, and the broken line is the attenuation value. It can be seen from the figure that compared with the use of CO 2 , using nitrous oxide for oxygen doping to obtain an N-type microcrystalline silicon layer, the battery performance decays more slowly and has better stability.
[0148] As can be seen from the above, the present invention uses laughing gas to replace the CO of prior art. 2 , in situ oxygen doping of the microcrystalline silicon layer during its manufacturing process can realize the manufacture of an oxygen-doped P-type microcrystalline silicon layer or an N-type microcrystalline silicon layer; by using N 2 O effectively improves the crystallinity and conductivity of the microcrystalline silicon layer, avoiding the 2 Dissociation causes the C content in the film to increase, resulting in poor film quality and high battery attenuation. 2 O is easier to dissociate, which can effectively increase the coating speed, which is beneficial to increasing production capacity and reducing costs.
[0149] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0150] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0151] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0152] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a microcrystalline silicon layer, characterized in that: The preparation method comprises: In the process of preparing the microcrystalline silicon layer, N2O is used as an oxygen source for oxygen doping.
2. The preparation method according to claim 1, characterized in that: The microcrystalline silicon layer is prepared using silane and hydrogen as raw materials; the flow ratio of the silane to the hydrogen is 1:(30-500); the flow ratio of the silane to the N2O is 100:(1-100).
3. The preparation method according to claim 2, characterized in that: Simultaneously with the oxygen doping, performing P-type doping or N-type doping using a P-type doping source or an N-type doping source; The P-type doping source includes a boron source; the boron source includes borane; the flow ratio of the P-type doping source to silane is (1-80):100; The N-type doping source includes a phosphorus source; the phosphorus source includes phosphine; the flow ratio of the N-type doping source to silane is (50-900):
100.
4. A method for manufacturing a HJT solar cell, the method comprising: Silicon wafers are textured, intrinsic i layers are prepared on both sides, N-type layers are prepared on the front side, P-type layers are prepared on the back side, TCO layers are prepared on both sides, and electrodes are prepared on both sides to obtain HJT solar cells; The N-type layer and / or the P-type layer is an N-type microcrystalline silicon layer or a P-type microcrystalline silicon layer obtained by the preparation method according to any one of claims 1 to 3.
5. The preparation method according to claim 4, characterized in that: When a P-type doping source is used for P-type doping, a P-type microcrystalline silicon layer is obtained, and the thickness of the P-type microcrystalline silicon layer is 10 to 100 nm; when an N-type doping source is used for N-type doping, an N-type microcrystalline silicon layer is obtained, and the thickness of the N-type microcrystalline silicon layer is 5 to 40 nm.
6. The preparation method according to claim 5, characterized in that: The preparation method divides the microcrystalline silicon layer into at least two superimposed sublayers and prepares them sequentially; the first prepared sublayer close to the intrinsic i layer is not oxygen-doped, and the thickness of the first prepared sublayer accounts for 15% to 25% of the total thickness of the microcrystalline silicon layer.
7. The manufacturing method according to claim 5, characterized in that: The preparation method divides the microcrystalline silicon layer into at least three superimposed sublayers and prepares them sequentially; the first prepared sublayer close to the intrinsic i layer and the last prepared sublayer away from the intrinsic i layer are not oxygen-doped, and the remaining sublayers are oxygen-doped using N2O as an oxygen source.
8. The manufacturing method according to claim 7, characterized in that: The thickness of the first sublayer prepared is 2 to 20 nm, the thickness of the middle sublayer is 2 to 45 nm, and the thickness of the last sublayer prepared is 3 to 35 nm.
9. The preparation method according to claim 4, characterized in that: The oxygen doping amount of the N-type microcrystalline silicon layer is greater than the oxygen doping amount of the P-type microcrystalline silicon layer.
10. The manufacturing method according to any one of claims 4 to 9, characterized in that: The manufacturing method also includes injecting LED light into the obtained HJT solar cell to repair film damage.
11. A HJT solar cell, characterized in that: The method is obtained by using the manufacturing method described in any one of claims 4 to 10.